2021
DOI: 10.1080/21870764.2020.1864897
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3/glass/hBN composites with high thermal conductivity and low dielectric constant for low temperature cofired ceramic applications

Abstract: To cite this article: Oğuzhan Bilaç & Cihangir Duran (2021): Al 2 O 3 /glass/hBN composites with high thermal conductivity and low dielectric constant for low temperature cofired ceramic applications, Journal of Asian Ceramic Societies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Therefore, it can be inferred that the hBN phase itself effectively optimized both microstructure and density, as well as dielectric and thermal properties. Thus, the G12BN@770 sample has comparable dielectric and thermal properties to similar products reported in previous studies, with a densification temperature of 770 • C [48]. On the other hand, the highest dielectric constant, of 4.43, was obtained for the G6BN@770.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, it can be inferred that the hBN phase itself effectively optimized both microstructure and density, as well as dielectric and thermal properties. Thus, the G12BN@770 sample has comparable dielectric and thermal properties to similar products reported in previous studies, with a densification temperature of 770 • C [48]. On the other hand, the highest dielectric constant, of 4.43, was obtained for the G6BN@770.…”
Section: Resultssupporting
confidence: 78%
“…The obtained results were compared to commercially produced LTCC glass-ceramics sintered at 800–900 °C, which also used B 2 O 3 to lower the sintering temperature. It was observed that they had comparable thermal conductivity values (2.0–4.9W/m.K) to those in the present study [ 26 , 48 , 49 ]. Other commercial products with similar glass-ceramic compositions have dielectric constants between ~ 4 and 5 [ 50 , 51 ].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, glass-ceramics’ excellent heat conductivity and their composites contribute to this result since no Al 2 O 3 or ZrO 2 degradation was detected due to the sintering temperature and preparation techniques used. According to the previous literature, AlN, Si 3 N 4 , SiC, and BN have also been used instead of Al 2 O 3 and ZrO 2 [ 15 , 21 , 23 , 34 ]. However, glass-ceramics with ZrO 2 additives show a more effective way to contribute to composites than Al 2 O 3 by comparing their thermal conductivity values with different glass-ceramic content [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies 21,22 processing and properties of the (CaO-SiO 2 -Al 2 O 3 -based) glass/mullite and glass/Al 2 O 3 composites for the LTCC applications were investigated as a function of glass (50-60 wt%) and nano h-BN (1-10 wt%) filler contents. Dense mullite/glass (55 wt%) composite with 10 wt% hBN addition was successfully engineered and had optimized dielectric and thermal properties.…”
Section: Introductionmentioning
confidence: 99%